Hukum Suntik Medis Saat Berpuasa: Analisis Fikih Terhadap Pendekatan Tekstual Dan Substansial - Veni Sofia; Muhammad Dani; Zainal Abidin; Ali Imran Sinaga (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2026)
This study aims to analyze the legality of medical injections during fasting from an Islamic jurisprudence perspective by examining two main approaches: textual and substantial. The research arises from contemporary issues caused by the development of medical technology, which has introduced modern treatment methods such as injections that are not explicitly discussed in classical fiqh literature. Using a qualitative method with a library research approach, this study draws on classical fiqh texts, contemporary literature, and related scientific journals. Data were analyzed inductively through a review of concepts, arguments, and the legal istinbath methods used by scholars. The findings reveal two main trends in understanding the legality of medical injections during fasting. The textual approach argues that injections do not invalidate the fast because they do not enter through natural channels (al-manafiz al-ma‘rufah), such as the mouth and nose, and are not categorized as eating or drinking. In contrast, the substantial approach holds that injections may invalidate the fast if they function as substitutes for eating and drinking, particularly nutritional injections. Therefore, classifying the type of injection is crucial in determining its legal ruling. This study concludes that an integrative-substantial approach is more relevant for addressing contemporary issues by distinguishing between nutritional and non-nutritional injections. Non-nutritional injections do not invalidate the fast, whereas nutritional injections do. These findings contribute to the development of more contextually grounded contemporary Islamic jurisprudence and provide practical guidance for Muslims and medical professionals in observing the fast without neglecting health considerations.